2018
DOI: 10.1007/s11262-018-1610-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hepatitis B virus in blood donors in Botswana

Abstract: Hepatitis B virus (HBV) poses a significant threat to blood transfusion safety in sub-Saharan Africa (SSA) where allogeneic blood donations are screened serologically, and more sensitive nucleic acid tests (NATs) are utilized infrequently. HBV strains circulating among blood donors in Botswana are not yet characterized. We designed a cross-sectional study to determine the HBV subgenotypes and prevalence of hepatitis B surface antigen (HBsAg) among blood donors between November 2014 and October 2015. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
(56 reference statements)
2
28
0
Order By: Relevance
“…Others have reported a 10-fold increased progression to HCC among HBV patients infected with genotype A compared to genotype D and that patients infected with genotype A strains were likely to progress to CHB compared to genotype D [8,80]. Most countries in SSA, including Botswana, have low prevalence of HBV genotype D3 among different risk groups than genotype A1 [25][26][27]81].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have reported a 10-fold increased progression to HCC among HBV patients infected with genotype A compared to genotype D and that patients infected with genotype A strains were likely to progress to CHB compared to genotype D [8,80]. Most countries in SSA, including Botswana, have low prevalence of HBV genotype D3 among different risk groups than genotype A1 [25][26][27]81].…”
Section: Discussionmentioning
confidence: 99%
“…Three sequence datasets were included in the current analysis. The first database (N 1 ) was used to map epitopes (epi) that bind predominantly to HLA class II alleles in Botswana and consisted of 92 non-recombinant full-length S gene (PreS/S) sequences [25,26,28] retrieved from GenBank (accession numbers MF979142-MF979176, KR139743-KR139748, and MH464807-MH464854). The aligned sequences were sorted by genotype and included A (n = 44) and D (n = 48).…”
Section: Mapping Peptides From Hbv Surface Gene Restricted To Hla-clamentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences were aligned in Clustal X version 2.1. Additional phylogenetic inference was conducted using the Bayesian Markov chain Monte Carlo (MCMC) in the Bayesian Evolutionary Sampling Trees (BEAST) version 1.7.5 as described previously [8, 14]. Posterior probabilities > 80% were deemed statistically significant.…”
Section: Methodsmentioning
confidence: 99%
“…In Africa, a range in prevalence from 1.7 to 14.7% has been reported [2–5]. In Botswana, preliminary studies reported a low HCV seroprevalence of below 1% [68] although Botswana is endemic for both human immunodeficiency virus (HIV) and hepatitis B virus (HBV) with the prevalence of HIV/HBV co-infection ranging from 4 to 10.6% [6, 7].…”
Section: Introductionmentioning
confidence: 99%